Stereodivergent approach in the protected glycal synthesis of L-vancosamine, L-saccharosamine, L-daunosamine and L-ristosamine involving a ring-closing metathesis step - Nocquet, Pierre-Antoine; Macé, Aurélie; Legros, Frédéric; Lebreton, Jacques; Dujardin, Gilles; Collet, Sylvain; Martel, Arnaud; Carboni, Bertrand; Carreaux, François (Beilstein Journal of Organic Chemistry, 2018)
In this paper, a new access to several chiral 3-aminoglycals as potential precursors for glycosylated natural products is reported from a common starting material, (−)-methyl-L-lactate. The stereodivergent strategy is based on the implementation of a ring-closing metathesis of vinyl ethers as key step of reaction sequences developed.
Keywords: 3-amino glycals; diastereoselective additions to aldehydes; pluramycins; ring-closing metathesis; vinyl ethers